Exogenous group G Streptococcus endophthalmitis following intravitreal ranibizumab injection - Kugu S (Dove Medical Press, 2012)
Suleyman Kugu,1 Mehmet Sahin Sevim,2 Nilufer Zorlutuna Kaymak,1 Gurkan Erdogan,3 Baran Kandemir,1 Omer Kamil Dogan41Lutfi Kirdar Kartal Training and Research Hospital, Eye Clinic, Istanbul, 2Haydarpasa Numune Training and Research Hospital, Eye Clinic, Istanbul, 3Umraniye Training and Research Hospital, Eye Clinic, Istanbul, 4World Eye Hospital, Eye Clinic, Istanbul, TurkeyAbstract: We report a case of group G Streptococcus endophthalmitis following an intravitreal ranibizumab injection for a choroidal neovascular membrane. Pars plana vitrectomy was applied for endophthalmitis and group G Streptococcus cultures were isolated in the vitreous samples taken from the patient. Twenty-four hours following pars plana vitrectomy the patient underwent myocardial infarction and cardiac arrest. To our knowledge this is the first reported case of group G Streptococcus endophthalmitis following an intravitreal injection.Keywords: group G Streptococcus, endophthalmitis, intravitreal injection